Dynamic reconstruction of the spine - Kim, Daniel H.; Sengupta, Dilip K.; Cammisa, Frank P. Jr; Yoon, Do Heum; Fessler, Richard G. (Thieme, 2015)
"Dynamic Reconstruction of the Spine, Second Edition, is an up-to-date, comprehensive resource on the instrumentation, technologies, and fundamental science integral to achieving spine motion preservation and stabilization. This revised text covers not only the latest technologies and surgical approaches, including MIS techniques, but also significantly more detail on the clinical biomechanics of the spine than the previous edition. Readers will appreciate the guidance this book provides on how to: successfully adopt new technology, find appropriate indications, address common safety and efficacy issues, and answer health economics questions for ethics committees and payers. Key Features: A substantial revision, with entirely new chapters in three quarters of the book, including a large section on basic as well as more advanced biomechanics topics. Highly visual - contains 20% more figures than the previous edition. Discusses and explains current advances in genetic and molecular technologies used to repair the spinal disc Includes an unbiased critique of the pro cons, clinical outcomes, and comparative outcomes of different devices. This new edition is an indispensable reference for orthopedic surgeons, neurosurgeons, and radiologists, as well as residents and fellows seeking the latest information on the technologies used in spine motion preservation and stabilization"--Provided by publisher